Resignificación de los elementos identitarios de la Parroquia San Antonio de Pichincha a través del desarrollo de productos indumentarios - Pacheco Miguez, Dayana Michelle (2023)
The tourism in the San Antonio de Pichincha parish, largely driven by the presence of the Middle of the World Monument, has exerted a significant influence both nationally and internationally. However, the predominant association with the monument has overshadowed the parish's own name and other cultural attractions. Despite possessing a valuable heritage, inadequate promotion has rendered these places relatively unnoticed by visitors. Given the substantial influx of tourists, shops situated near tourist attractions actively endorse artisanal products, including clothing, as tangible memorabilia. Nonetheless, a meticulous examination reveals that many textile designs are influenced by foreign cultures, reflecting an adaptation over the years within the weaving industry. This project aims to reevaluate the parish's identity elements within apparel design, drawing the interest of visitors and fostering exploration of lesser-known attractions. In addition to accentuating San Antonio de Pichincha's identity, it seeks to instill a sense of cultural belonging among the local community and provide economic and touristic opportunities, thereby enriching the visitor experience and promoting a genuine appreciation of the parish's cultural richness.